Public preferences for biomass electricity in China. (November 2018) - Zhao, Xiaoli; Cai, Qiong; Li, Shujie; Ma, Chunbo
Abstract: The Chinese government has made significant effort to promote biomass based electricity generation in recent years. Yet, little is known about consumers' preferences for biomass electricity and associated environmental impacts. This paper uses discrete choice experiments (DCE) to investigate Chinese consumers' preference for electricity generated from various biomass sources. Based on 548 responses, the paper finds that Chinese households are willing to pay a premium of around 27 Yuan per month or 0.20 Yuan per kilowatt hour (kWh) to replace coal-fired electricity. Among the various biomass sources, electricity generated from agricultural and forestry biomass is most preferred, followed by biogas electricity and waste-to-energy. It is also found that respondents have a significant willingness to pay for reducing haze. Consumers' household structure and environmental awareness also affect their preference for biomass electricity. These results have significant implications for the prioritization, design and communication of biomass promoting schemes. Highlights: We explore preferences for electricity sourced from various biomasses in China. Among all biomass sources, agricultural and forestry biomass is most preferred. Waste-to-energy is the least preferred technology option. Respondents are most concerned with haze effect of electricity generation. Overall, WTP for biomass electricity is over one third of typical bill.